Application of the International Accounting Standards (IAS) in Bangladesh: A Study on Habib Bank Limited, Bangladesh - Uddin, Muhammad Salah (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.